Effective awe-inspiring visual content strategy for social media engagement with ethical fashion brands: the mediating role of deontological ethical beliefs - Pu, Weilin (Journal of business ethics, 2025)
The demand for ethical fashion products has grown in recent years, with consumers caring more about how the product is made. Based on the deontological underpinnings of ethical fashion, the present research provides recommendations to ethical fashion brands by leveraging the emotion of awe through visual representations. This research examines 5362 Instagram posts of five ethical fashion brands and shows that the presence of awe-inspiring visual elements increases consumer engagement on social media for ethical fashion brands. Further, this research identifies the moderating roles of the color green and the size of the visual elements in this context. Two follow-up experiments provide causal evidence for these relationships. Experimental evidence for the role of deontological beliefs as a mediator of the relationship between feelings of awe and social media engagement with ethical fashion brands is also provided. Overall, the findings offer a more nuanced understanding of how ethical fashion brands can develop effective visual advertising campaigns on social media and the underlying process driving the effect, which is consistent with deontological ethics.